Resilient and sensitive key points of the photosynthetic machinery of coffea spp. to the single and superimposed exposure to severe drought and heat stresses - Dubberstein, Danielly (2021)
This study unveils the single and combined drought and heat impacts on the photosynthetic performance ofCoffea arabicacv. Icatu andC. canephoracv. Conilon Clone 153 (CL153). Well-watered (WW) potted plants were gradually submitted to severe water deficit (SWD) along 20 days under adequate temperature (25/20 degrees C, day/night), and thereafter exposed to a gradual temperature rise up to 42/30 degrees C, followed by a 14-day water and temperature recovery. Single drought affected all gas exchanges (includingA(max)) and most fluorescence parameters in both genotypes. However, Icatu maintainedF(v)/F(m)and RuBisCO activity, and reinforced electron transport rates, carrier contents, and proton gradient regulation (PGR5) and chloroplast NADH dehydrogenase-like (NDH) complex proteins abundance. This suggested negligible non-stomatal limitations of photosynthesis that were accompanied by a triggering of protective cyclic electron transport (CEF) involving both photosystems (PSs). These findings contrasted with declines in RuBisCO and PSs activities, and cytochromes (b(559),f,b(563)) contents in CL153. Remarkable heat tolerance in potential photosynthetic functioning was detected in WW plants of both genotypes (up to 37/28 degrees C or 39/30 degrees C), likely associated with CEF in Icatu. Yet, at 42/30 degrees C the tolerance limit was exceeded. ReducedA(max)and increasedC(i)values reflected non-stomatal limitations of photosynthesis, agreeing with impairments in energy capture (F(0)rise), PSII photochemical efficiency, and RuBisCO and Ru5PK activities. In contrast to PSs activities and electron carrier contents, enzyme activities were highly heat sensitive. Until 37/28 degrees C, stresses interaction was largely absent, and drought played the major role in constraining photosynthesis functioning. Harsher conditions (SWD, 42/30 degrees C) exacerbated impairments to PSs, enzymes, and electron carriers, but uncontrolled energy dissipation was mitigated by photoprotective mechanisms. Most parameters recovered fully between 4 and 14 days after stress relief in both genotypes, although some aftereffects persisted in SWD plants. Icatu was more drought tolerant, with WW and SWD plants usually showing a faster and/or greater recovery than CL153. Heat affected both genotypes mostly at 42/30 degrees C, especially in SWD and Icatu plants. Overall, photochemical components were highly tolerant to heat and to stress interaction in contrast to enzymes that deserve special attention by breeding programs to increase coffee sustainability in climate change scenarios.